2018
DOI: 10.1111/hequ.12165
|View full text |Cite
|
Sign up to set email alerts
|

International and transnational education for whose interests? A study on the career development of Chinese students

Abstract: A significant increase in internationally mobile students has been observed in the past decades. With the strong intention of enhancing their competitiveness in the global labour market, a growing number of students have embarked on their learning journeys through studying abroad or enrolling in transnational Higher Education programmes. These students expect the international learning experience will enhance their future job prospects and career advancement. However, whether or not this learning experience en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 30 publications
(31 reference statements)
1
22
0
2
Order By: Relevance
“…A survey by Mok et al (2018) of Chinese IBC graduates found that the majority of the students perceived that a transnational education had facilitated their career development, and at one IBC, 94% of graduates were in employment within six months of graduation. In a similar survey of IBC students conducted in Malaysia, the students perceived substantial enhancement of their employability skills, particularly the ability to work independently, Two decades of IBC development, 2000-2020 command of English, adaptability, subject knowledge and expertise, team working skills and analytical/problem-solving skills (Belderbos, 2019).…”
Section: Knowledge Skills and Innovationmentioning
confidence: 99%
“…A survey by Mok et al (2018) of Chinese IBC graduates found that the majority of the students perceived that a transnational education had facilitated their career development, and at one IBC, 94% of graduates were in employment within six months of graduation. In a similar survey of IBC students conducted in Malaysia, the students perceived substantial enhancement of their employability skills, particularly the ability to work independently, Two decades of IBC development, 2000-2020 command of English, adaptability, subject knowledge and expertise, team working skills and analytical/problem-solving skills (Belderbos, 2019).…”
Section: Knowledge Skills and Innovationmentioning
confidence: 99%
“…The advantages of TNE include providing students with high-quality educational experiences, development of students' critical thinking abilities and intercultural skills, engagement with rich and diversified content and students' understanding of international business environment (Smith, 2010). Prior research has shown that career development, acquiring hard knowledge, development of soft skills and the development of cross-cultural understanding represent some of the experiences that Source(s): Graduate School, GTUC students gather through TNE (Mok et al, 2018). Correspondingly, reports of positive students' feedback on their academic and support services satisfaction are likely to increase the participation rates of students in TNE (Nnazor, 2018).…”
Section: Gains In Tnementioning
confidence: 99%
“…While transnational education promises an expansion of opportunities for governments and individuals to access education, concerns about the relevance and quality of it have led many to criticise and question its sustainability. The literature indicates three main concerns with it as: (a) a form of Western academic imperialism (Abbott, 2017;Tikly, 2013), (b) a form of "academic capitalism" (McBurnie & Ziguras, 2009;Tikly, 2013), and (c) a contributor to global inequality (Altbach, 2013;Little, 2000;McGrath, 2002;Mok, Han, Jiang & Zhang, 2018). Underlining these concerns is the conviction that transnational education involves the uncritical transfer of educational policy from the Western world to the developing world for economic and political reasons (Abbott, 2017;Tikly & Barrett, 2011;McGrath, 2002).…”
Section: Sustainability Of Transnational Educationmentioning
confidence: 99%